2014
DOI: 10.5430/afr.v3n4p71
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Management Accounting Practices in Emerging Telecommunication Market in Ghana

Abstract: The ever-increasing importance of telecommunication companies in Ghana coupled with global and domestic competitions, increasing cost and decreasing profitability was the impetus for this study. This research examines the application of a broad range of management accounting practices used by telecommunication companies in Ghana. It sought to establish the extent of use and reasons for the adoption of Management Accounting Practices (MAPs) in Ghana mobile telecom industry (GMTI). This study was a cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 38 publications
3
18
0
Order By: Relevance
“…The research findings revealed that MAPs are affected by organization size and advanced production technology. As per previous research, organization size was found to have a positive and significant relationship with MAPs (Ahmad, 2012;Mbawuni & Anertey, 2014;Ismail & Mahmoud, 2012). As such, more attention should be given by the government, public and private sector as well as accounting bodies to develop appropriate policies and procedures to allow for better adoption of MAPs.…”
Section: Discussion Of Findingssupporting
confidence: 77%
See 1 more Smart Citation
“…The research findings revealed that MAPs are affected by organization size and advanced production technology. As per previous research, organization size was found to have a positive and significant relationship with MAPs (Ahmad, 2012;Mbawuni & Anertey, 2014;Ismail & Mahmoud, 2012). As such, more attention should be given by the government, public and private sector as well as accounting bodies to develop appropriate policies and procedures to allow for better adoption of MAPs.…”
Section: Discussion Of Findingssupporting
confidence: 77%
“…Also, majority of the manufacturing firms in Egypt prefer to adopt traditional MAPs because traditional MAPs are simple and are convenient to use. Finally, in the research by Mbawuni and Anertey (2014) examining MAPs in telecommunication companies in Ghana, it was found that the extent of the usage and reasons for adoption of MAPs in Ghana depended on the nature and organization size.…”
Section: Relationship Between Organization Size and Management Accounmentioning
confidence: 99%
“…Budgeting practices were the predominate practice in the management control systems of American businesses (McLellan, 2014) and (Abdel-Kader & Luther, 2006) in UK. Moreover, in other less developed countries such in Ghana (Mbawuni & Anertey, 2014) Pakistan (Ashfaq, Younas, Usman, & Hanif, 2014); Vietnamese (Ngoc Phi Anh et al, 2011). In Greece,budgeting for planning financial position, and budgeting for controlling costs have been ranked highly in usage before and during the crisis.…”
Section: Planning and Budget Practicesmentioning
confidence: 99%
“…While the contemporary activity-based budgeting (ABB) is ranked moderately adopted in Ghana (Mbawuni & Anertey, 2014) Thus, the main conclusion of the majority of the studies was that traditional budget practices are still widely used and important even in the most developed countries.Both traditional and contemporary budgeting practices are included in research MAPs list.…”
Section: Planning and Budget Practicesmentioning
confidence: 99%
“…First, currently the use of SMAP is unavoidable especially among local manufacturing enterprises in Nigeria due to their abysmal performance over the years, and as a result of faulty decision making occasioned by reliance on the outdated traditional management accounting information (Egbunike et al, 2014;Rababa'h, 2014;Akenbor & Okoye, 2012). Also, relationship between SMAP adoption and benefits accruable to enterprises have resulted in mixed research findings (Alsoboa et al, 2015;Ojra, 2014;Ahmad & Leftesi, 2014;Ramljak & Rogosic, 2012;Mbawuni & Anertey, 2014). In covering this research gap, this paper makes contributions to the literature on the subject matter.…”
Section: Introductionmentioning
confidence: 96%